Observation of Measles Virus Cell-to-Cell Spread in Astrocytoma Cells by Using a Green Fluorescent Protein-Expressing Recombinant Virus - Duprex, W. Paul (American Society for Microbiology, 1999)
A recombinant measles virus (MV) which expresses enhanced green fluorescent protein (EGFP) has been rescued. This virus, MVeGFP, expresses the reporter gene from an additional transcription unit which is located prior to the gene encoding the measles virus nucleocapsid protein. The recombinant virus was used to infect human astrocytoma cells (GCCM). Immunocytochemistry (ICC) together with EGFP autofluorescence showed that EGFP is both an early and very sensitive indicator of cell infection. Cells that were EGFP-positive and ICC-negative were frequently observed. Confocal microscopy was used to indirectly visualize MV infection of GCCM cells and to subsequently follow cell-to-cell spread in real time. These astrocytoma cells have extended processes, which in many cases are intimately associated. The processes appear to have an important role in cell-to-cell spread, and MVeGFP was observed to utilize them in the infection of surrounding cells. Heterogeneity was seen in cell-to-cell spread in what was expected to be a homogeneous monolayer. In tissue culture, physical constraints govern the integrity of the syncytia which are formed upon extensive cell fusion. When around 50 cells were fused, the syncytia rapidly disintegrated and many of the infected cells detached. Residual adherent EGFP-positive cells were seen to either continue to be involved in the infection of surrounding cells or to remain EGFP positive but no longer participate in the transmission of MV infection to neighboring cells.